Vesicular CLC chloride/proton exchangers in health and diseases - Picollo, Alessandra (Frontiers in Pharmacology, 2023)
Chloride is one of the most abundant anions in the human body; it is implicated in several physiological processes such as the transmission of action potentials, transepithelial salt transport, maintenance of cellular homeostasis, regulation of osmotic pressure and intracellular pH, and synaptic transmission. The balance between the extracellular and intracellular chloride concentrations is controlled by the interplay of ion channels and transporters embedded in the cellular membranes. Vesicular members of the CLC chloride protein family (vCLCs) are chloride/proton exchangers expressed in the membrane of the intracellular organelles, where they control vesicular acidification and luminal chloride concentration. It is well known that mutations in CLCs cause bone, kidney, and lysosomal genetic diseases. However, the role of CLC exchangers in neurological disorders is only now emerging with the identification of pathogenic CLCN gene variants in patients with severe neuronal and intellectual dysfunctions. This review will provide an overview of the recent advances in understanding the role of the vesicular CLC chloride/proton exchangers in human pathophysiology.